Assessment of pulmonary venous stenosis after radiofrequency catheter ablation for atrial fibrillation by magnetic resonance angiography: A comparison of linear and cross-sectional area measurements - Tintera, Jaroslav; Porod, Václav; Cihák, Robert; Mlcochová, Hanka; Rolencová, Eva; Fendrych, Pavel; Kautzner, Josef (European radiology, 2006)
One of the recognised complications of catheter ablation is pulmonary venous stenosis. The aim of this study was to compare two methods of evaluation of pulmonary venous diameter for follow-up assessment of the above complication: (1) a linear approach evaluating two main diameters of the vein, (2) semiautomatically measured cross-sectional area (CSA). The study population consists of 29 patients. All subjects underwent contrast-enhanced magnetic resonance angiography (CeMRA) of the pulmonary veins (PVs) before and after the ablation; 14 patients were also scanned 3 months later. PV diameter was evaluated from two-dimensional multiplanar reconstructions by measuring either the linear diameter or CSA. A comparison between pulmonary venous CSA and linear measurements revealed a systematic difference in absolute values. This difference was not significant when comparing the relative change CSA and quadratic approximation using linear extents (linear approach). However, a trend towards over-estimation of calibre reduction was documented for the linear approach. Using CSA assessment, significant PV stenosis was found in ten PVs (8%) shortly after ablation. Less significant PV stenosis, ranging from 20 to 50% was documented in other 18 PVs (15%). CeMRA with CSA assessment of the PVs is suitable method for evaluation of PV diameters.
Keywords: senioři; Meglumine; Reproducibility of Results; Pulmonary Veins; meglumin; organokovové sloučeniny; stenóza pulmonální chlopně; Contrast Media; reprodukovatelnost výsledků; Male; počítačové zpracování obrazu; katetrizační ablace; Phantoms, Imaging; Middle Aged; mužské pohlaví; kontrastní látky; studie případů a kontrol; Adult; magnetická rezonanční angiografie; Pulmonary Valve Stenosis; Catheter Ablation; ženské pohlaví; fantomy radiodiagnostické; Humans; Organometallic Compounds; venae pulmonales; fibrilace síní; lidé středního věku; Image Processing, Computer-Assisted; dospělí; Female; Aged; Atrial Fibrillation; Magnetic Resonance Angiography; lidé; Case-Control Studies